2021
DOI: 10.1037/pla0000148
|View full text |Cite
|
Sign up to set email alerts
|

Implementing play and language therapy to work with preschool children with language and behavioral issues.

Abstract: Communicating thoughts and needs is one of the most essential components of being human. In the United States, 6.4 million preschool-age children are diagnosed with a language disorder (American Speech-Language-Hearing Association, 2019). Many of these children also exhibit co-morbid behavior issues. Difficulties with effective communication and behavior can result in academic, social, and personal issues for these children (Balch & Ray, 2015). While speech-language pathologists (SLPs) are well versed in provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…Therefore, the second hypothesis of the study is confirmed. These findings are consistent with results from previous studies (Abdollahian et al, 2013;Adamiat et al, 2019;Davis & Barnes, 2021;Faramarzi & ghanei, 2020;Farnam et al, 2020;Fattahi Andebil et al, 2018;Kumar et al, 2022;Mahmoodi et al, 2022;Mehrafza et al, 2022;Perryman & Bowers, 2018;Sarah et al, 2021;Thomas et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, the second hypothesis of the study is confirmed. These findings are consistent with results from previous studies (Abdollahian et al, 2013;Adamiat et al, 2019;Davis & Barnes, 2021;Faramarzi & ghanei, 2020;Farnam et al, 2020;Fattahi Andebil et al, 2018;Kumar et al, 2022;Mahmoodi et al, 2022;Mehrafza et al, 2022;Perryman & Bowers, 2018;Sarah et al, 2021;Thomas et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…Given that the presence of fear, anxiety, and psychological issues in children can hinder the care and follow-up of treatment (Ahlen et al, 2018;Egbe et al, 2023), attention to therapeutic methods, especially in preschool ages, becomes crucial for reducing psychological problems in children. Psychotherapists use various treatments for anxiety and psychological problems in children, including cognitive-behavioral therapy, family therapy, and play therapy (Davis & Barnes, 2021). The cognitive-behavioral approach is based on three assumptions: an individual's behavior is influenced by thoughts, imaginations, perceptions, and other cognitive events; individuals play an active role in their learning and create some of their environment; and for cognitive constructs to be useful in individual efforts to change behavior, cognitive and behavioral involvement must be realized practically (Murray, 2015).…”
Section: Introductionmentioning
confidence: 99%